The complex fossil magnetic field of the δ Scuti star HD 41641. Issue 2 (5th November 2020) - Thomson-Paressant, K; Neiner, C; Zwintz, K; Escorza, A
ABSTRACT: Only three magnetic δ Scuti stars are known as of today. HD 41641 is a δ Scuti star showing chemical peculiarities and rotational modulation of its light curve, making it a good magnetic candidate. We acquired spectropolarimetric observations of this star with NARVAL at Télescope Bernard Lyot (TBL) to search for the presence of a magnetic field and characterize it. We indeed clearly detect a magnetic field in HD 41641, making it the fourth known magnetic δ Scuti star. Our analysis shows that the field is of fossil origin, like magnetic OBA stars, but with a complex field structure rather than the much more usual dipolar structure.